Executive compensation and firm risk: an examination across industries. Issue 3 (24th August 2018) - Abrokwah, Stephen; Hanig, Justin; Schaffer, Marc
Abstract : Purpose: This paper aims to examine the impact of executive compensation on firm risk-taking behavior, measured by the volatility of stock price returns. Specifically, this analysis explores three hypotheses. First, the impact of short-term and long-term executive compensation packages on firm risk is analyzed to assess whether the packages incentivize risk-taking behavior. Second, the authors test how these compensation and risk relationships were impacted by the financial crisis. Third, they expand the analysis to see if the relationship varies across different industries. Design/methodology/approach: The econometric approach used to examine the executive compensation and firm risk relationship takes the form of two different panel model specifications. The first model is a pooled model using the panel data of executive compensation, the firm-level control variables and volatility of stock market returns. The second model highlights the differences in the relationship between executive compensation and riskiness of firm behavior across industries. Findings: The authors find a significant and robust relationship, showing that during the post-financial crisis period firms tended to use long-term compensation shares to reduce firm risk. They also find that the relationship between various compensation components and firm risk varies across industries. Specifically, the bonus share of compensation negatively impacted firm risk in the financial services industry, while it positively impacted risk in the transportation, communication, gas, electric and services sectors. Additionally, long-term compensation share exhibits an inverse relationship with firm risk in the financial services, manufacturing and trade industries. Originality/value: The conclusions of this paper suggest that there is indeed a relationship between executive compensation and firm risk across industries. There was a notable change in the relationship however between firm risk and long-term compensation following the financial crisis, where firms used long-term compensation to reduce firm riskiness. In other words, the financial crisis changed the nature of this relationship across S&P 1500 firms. The last key finding is that there exist differences in risk and compensation relationships across industries, and these differences across industries are highlighted across both bonus share and long-term incentive share variables. This is the first study to explore this relationship across industries.